Energy platforms using digital modular substations and power units for Arctic - Shulga R.N.; Petrov A.Yu.; Hrennikov A. Y. (LLC Center for Information and Legal Support for the Development of the Arctic, 2020)
The description of energy platforms in the form of SAE using digital modular substations and power units is presented. Samples of electrical equipment used for the implementation of these substations are given. Two directions of implementation are considered: CMP as AC and DC CMP in DC. The part of the DSM as describes the structure according to the IEC 61850 Protocol, samples of digital current and voltage sensors, complete switchgears, containers of static compensators are given. In the part of the DC CMC, the structure is given, static converters, and electric power storage devices of hydrogen and electrochemical types are described. The scope of application of both types of substations is considered and the advantages of implementing DC CMC for providing reliable power supply in the conditions of natural and man-made accidents are noted.